Talāq Kināyah in the Perspective of the Hanafi and Maliki Madhhabs: Implications for Contemporary Islamic Jurisprudence - Mahdiana, Riska; Alamsyah,; Pradikta, Hervin Yoki (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2025)
The purpose of this study is to examine and uncover the substantive views of the Hanafi and Maliki schools of thought regarding talak kinayah, to identify the similarities and differences between these two schools, and to analyze the legal implications of talak kinayah on contemporary fiqh. This study employs a qualitative research method. It is descriptive-comparative in nature and uses library research as its type of study. The data are analyzed through the perspective of maqashid shariah to observe the implications of talak kinayah on contemporary fiqh. The study finds that both Imams acknowledge that talak kinayah can be used to pronounce divorce, but they differ in the requirement of intention (niyyah); the Hanafi school assesses the validity of talak kinayah based on context and situation, whereas the Maliki school requires a clear intention or evident signs (qarinah). In contemporary practice, this difference influences the determination of divorce legal status, for example, in cases of verbal talak or those conveyed through electronic media. This study contributes to the development of Islamic family law and serves as a foundation for adaptive legal regulations addressing non-formal divorces in the contemporary era.